Development of an Integrated Computer Aided Design Tool for Microirrigation Systems - Fouial, Abdelouahid (2001)
Planning, design and management of microirrigation systems require extensive numerical calculations. The introduction of computers in these processes removes much of the complications in calculation and results in more accurate analysis. Not many of the available software can be used to deal with an overall irrigation system implementation. Usually, separate software are used for irrigation planning and irrigation systems design. Consequently, this increases the investment cost for using the software in irrigation schemes. Hence, an integrated approach for both planning and system design is required. In this study, an integrated computer aided design for microirrigation systems was developed. The program was written in Visual Basic (version 6.0) and it runs in Windows environment. A user-friendly interface is provided to give more flexibility to the user. This program uses menu bar and toolbar which takes the user to all data entry and results dialogs. Additionally, it is designed in such a way that extensive use of tables tables and graphics will be provided. This program also provides a help file that can be used as a guide for selecting the appropriate data during data entry processes. The developed program has the ability to estimate crop water requirements and design of microirrigation system pipelines. The computation of reference crop evapotranspiration from the available climatic data can be done for daily and monthly time steps, using F AO Penman-Monteith method. Crop water requirement during the whole crop growing season can be calculated. Using these data, the program estimates irrigation requirement taking into consideration the available rainfall. All the inputted data and the obtained results can be displayed in tabular or graphical forms. The program is also capable of performing analysis of either lateral or submain unit. All the emitter flows along a lateral or in a submain unit can be determined. Additionally, maximum and minimum emitter flows and their locations can also be determined. Finally, emitter flow variation and pressure variation along a lateral or in a submain unit are computed. In this stage, tables and graphics are also provided. The overall laterals' layout and emitter flows profile can be displayed in the screen. The developed program can be considered as a tool for preliminary design of micro irrigation systems. It is recommended to extend it to more powerful software by including the design of all irrigation system.